INFORMATION SYSTEM FOR COLLECTING DATA FOR STUDENTS IN GREAT CHILDREN'S LITERACY (AHE) & BIMBEL HAPPY DAYS - Yuda Purnama Putra; Egi Badar Sambani (Journal of Multimedia Technology and Applied Software, 2024)
During the 2020-2022 Covid 19 pandemic, with limited meetings between students and teachers at school, automatically students' ability to receive material will be limited. With the lack of intensity of student meetings with teachers at school and the distance learning system, it will be an obstacle in achieving learning goals. Therefore, in Tasikmalaya City there are several tutoring institutions, one of which is Great Children's Literacy Tutoring (AHE) & Happy Days Tutoring. Great Children's Literacy Lessons (AHE) & Bimbel Happy Days is one of the tutoring places in Tasikmalaya which is located on Jl. Pataruman No. 36. Also, during a pandemic like this, Great Children's is Great Children's Literacy (AHE) & Happy Days Tutoring has experienced a significant increase, which has caused tutors to experience difficulties in the data collection process for students which takes a long time. Therefore, the author tries to build an information system that can store student data so that it is more effective in collecting data and does not take a long time by using the waterfall method. This system can speed up student data collection, making it more efficient. This system is quite effective to be used as an alternative solution for teachers in collecting student data.